2021
DOI: 10.21608/ejhc.2021.188207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of What Sapp Educational Program Reminder on Pregnant Women’s Knowledge , Attitude and Practice Regarding COVID -19 pandemic

Abstract: Background: Pregnant women is one of the most group who are at high risk for COVID-19 infection. To protect them should keep them away from exposure for infection and enhance their knowledge, attitude and practice about preventive measures towards COVID-19 pandemic. Aim of the Study: To evaluate the effect of whatsApp educational program reminder on pregnant women's knowledge, attitude and practice regarding COVID -19 pandemic. Research Design: Quasi experimental one group pre, post-test research design was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In one study, authors used telehealth and WhatsApp nursing educational programs using messages and then assessed pregnant women's knowledge, attitude, and practices toward COVID-19 [30]. Studies found that COVID-19 knowledge, attitude, and practices significantly improved after implementing the educational program [30,31]. Even though there is an international effort to increase awareness about the vaccine, there are scarce resources in the literature on providing an educational program to improve hesitancy toward COVID-19 vaccine among pregnant, planning for pregnancy, or breast-feeding mothers.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, authors used telehealth and WhatsApp nursing educational programs using messages and then assessed pregnant women's knowledge, attitude, and practices toward COVID-19 [30]. Studies found that COVID-19 knowledge, attitude, and practices significantly improved after implementing the educational program [30,31]. Even though there is an international effort to increase awareness about the vaccine, there are scarce resources in the literature on providing an educational program to improve hesitancy toward COVID-19 vaccine among pregnant, planning for pregnancy, or breast-feeding mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in terms of managing neck pain and voice alteration following thyroid surgery, the effectiveness is currently unknown (Hong et al, 2017). It is imperative to reorganize health education initiatives concerning primary healthcare providers and social media to enhance individuals' understanding and mitigate associated issues (Sabry et al, 2021). Through the use of social media platforms like Facebook, Instagram, WhatsApp, Snapchat, and Twitter, barriers to in-person communication can be overcome and continuous support and efficient communication can be provided.…”
Section: Introductionmentioning
confidence: 99%